2021
DOI: 10.1097/ceh.0000000000000331
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review and Narrative Synthesis: Determinants of the Effectiveness and Sustainability of Measurement-Focused Quality Improvement Trainings

Abstract: Introduction: The ability of health care professionals to measure change is critical for successful quality improvement (QI) efforts. Currently, there are no systematic reviews focusing on continuing education for health care professionals in data skills for QI. The purpose of this systematic review is to define effectiveness and sustainability of QI programs for health care professionals containing a measurement skills component and to identify barriers and facilitators to effectiveness and sustai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…In addition, results from an experiential training program in QI for Practicing Professionals, conducted over 10 years, revealed positive changes in clinical practice and benefits to patients. The program was well-received by trainees, who valued the acquired skills [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, results from an experiential training program in QI for Practicing Professionals, conducted over 10 years, revealed positive changes in clinical practice and benefits to patients. The program was well-received by trainees, who valued the acquired skills [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Kurshid et al 17 conducted a systematic review and narrative synthesis in an effort to define the effectiveness and sustainability of quality improvement programs for health care professionals containing a measurement skills component, and to identify barriers and facilitators to effectiveness and sustainability. Quality improvement (QI) is a key constituent in CPD that, nonetheless, has had its share of recent critiques concerning the need for improvement of reporting, methods, and forms of analysis.…”
Section: Adding To the Cpd Evidence Basementioning
confidence: 99%
“…JCEHP has provided some guidance on preparing such studies for publication, and I would encourage authors who intend to submit their CPD intervention studies to JCEHP to carefully follow the advice provided by our past and present expert Editorial Board members. [14][15][16] Kurshid et al 17 conducted a systematic review and narrative synthesis in an effort to define the effectiveness and sustainability of quality improvement programs for health care professionals containing a measurement skills component, and to identify barriers and facilitators to effectiveness and sustainability. Quality improvement (QI) is a key constituent in CPD that, nonetheless, has had its share of recent critiques concerning the need for improvement of reporting, methods, and forms of analysis.…”
Section: Adding To the Cpd Evidence Basementioning
confidence: 99%
“…A more recent realist-inspired review [27] confined itself to a specific type of QI, namely "QI collaboratives" to investigate contexts, mechanisms and outcomes but still included only five (out of 32) primary studies from LMICs. Still, other reviews have confined themselves to 'training and measurement' [28][29][30] and patient safety education [31,32]. No systematic review was found that synthesized literature from LMICs to inform holistic QI policy and practice specifically in PHC.…”
Section: Introductionmentioning
confidence: 99%